Irregular forest structures originating after fire: An opportunity to promote alternatives to even‐aged management in boreal forests. Issue 7 (9th May 2022) - Martin, Maxence; Leduc, Alain; Fenton, Nicole J.; Montoro Girona, Miguel; Bergeron, Yves; Valeria, Osvaldo
Abstract: Even‐aged silviculture based on short‐rotation clearcuts had severely altered boreal forests. Silvicultural alternatives (e.g. continuous cover or retention forestry) have the potential to restore and protect the habitats and functions of boreal forests. These alternatives are however often restricted to structurally complex old‐growth forest, which are particularly threatened by anthropogenic disturbances. Increasing the use of alternatives to even‐aged silviculture in early‐successional stands could help recruit more structurally complex forests, with characteristics closer to the old‐growth. In this article, we therefore evaluate the potential for silvicultural alternatives to even‐aged management in boreal forests that burned less than a century ago. We analysed 1085 field plots in a 243, 000 km 2 area situated in the boreal forest of eastern Canada. These plots burned 30–100 years before the survey and had not been subjected to previous or subsequent anthropogenic disturbance; they hence represent young primary forests. The main patterns of tree diameter distribution variation within the plots were identified using k ‐means clustering. Stand structure, tree species composition and environmental variables that most explained the differences among the clusters were identified with a random forest model, and then compared using Kruskal–Wallis and Fisher's exact tests. The majority (>75%) of the plots presented an irregular structure of stem diameters (i.e. non‐normally distributed, with many small diameter trees). The understorey was generally dominated by black spruce ( Picea mariana [Mill.] BSP), a shade‐tolerant species. Irregular structures were observed in both forests of high and low productivity, implying that different processes (e.g. early regeneration, variable tree growth) can lead to observed early irregular structure. Regular structures were generally characterized by a higher productivity and abundance in hardwood species compared to the irregular structures. Synthesis and applications . Many boreal forests of eastern Canada progress towards an irregular structure in the decades following the last stand‐replacing fire. A substantial part of these early‐successional forests may be suitable for alternatives to even‐aged silviculture that better maintains habitats and functions of preindustrial boreal forests. Abstract : Many boreal forests of eastern Canada progress towards an irregular structure in the decades following the last stand‐replacing fire. A substantial part of these early‐successional forests may be suitable for alternatives to even‐aged silviculture that better maintains habitats and functions of preindustrial boreal forests. Résumé: La sylviculture équienne basée sur des coupes totales à courte rotation a gravement dégradé les forêts boréales. Des alternatives sylvicoles (par exemple, la foresterie à couvert continu) ont le potentiel de restaurer et de protéger les habitats et fonctions des forêts boréales. Ces alternatives sont toutefois souvent limitées aux vieilles forêts à structure complexe, qui sont particulièrement menacées par les perturbations anthropiques. Augmenter utilisation des alternatives à la sylviculture équienne dans les peuplements en début de succession pourrait aider à recruter des forêts structurellement plus complexes, aux caractéristiques plus proches des vieilles forêts. Dans cet article, nous évaluons donc le potentiel des alternatives sylvicoles à la gestion équienne dans les forêts boréales qui ont brûlé il y a moins d'un siècle. Nous avons analysé 1085 placettes de terrain dans un territoire de 243, 000 km 2 situé dans la forêt boréale de l'Est du Canada. Ces placettes ont brûlé 30 à 100 ans avant l'inventaire et n'ont pas été soumises à des perturbations anthropiques antérieures ou ultérieures; elles représentent donc de jeunes forêts primaires. Les principaux patrons de distribution des diamètres des arbres au sein des placettes ont été identifiés à l'aide d'un regroupement de type k ‐moyennes. La structure du peuplement, la composition des espèces d'arbres et les variables environnementales qui expliquent le mieux les différences entre les groupes ont été identifiées à l'aide d'un modèle de forêt aléatoire, puis comparées à l'aide des tests de Kruskal‐Wallis et de Fisher. La majorité (>75%) des parcelles présentait une structure irrégulière des diamètres des tiges (c'est‐à‐dire une distribution non normale, avec de nombreux arbres de petit diamètre). Le sous‐étage était généralement dominé par l'épinette noire ( Picea mariana [Mill.] BSP), une espèce tolérante à l'ombre. Des structures irrégulières ont été observées dans les forêts de haute et de basse productivité, ce qui implique que différents processus (par exemple, régénération précoce, croissance variable des arbres) peuvent conduire aux structures irrégulières précoces observées. Les structures régulières étaient généralement caractérisées par une productivité et une abondance des espèces feuillues plus élevées par rapport aux structures irrégulières. Synthèse et applications: De nombreuses forêts boréales de l'est du Canada évoluent vers une structure irrégulière dans les décennies qui suivent le dernier feu sévère. Une partie substantielle de ces forêts en début de succession peut convenir à des alternatives à la sylviculture équienne, capables de mieux maintenir les habitats et les fonctions des forêts boréales préindustrielles.